1987
DOI: 10.1242/jcs.1987.supplement_8.12
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Plaques: Sites of Transmembrane Interaction Between the Extracellular Matrix and the Actin Cytoskeleton

Abstract: SUMMARYIn this paper we review what is known about the organization of adhesion plaques, the regions where cells in culture adhere most tightly to the underlying substratum. These specialized areas of the plasma membrane serve as attachment sites for stress fibres. A major objective has been to determine how microfilament bundles are anchored at such regions. In their morphology and composition adhesion plaques resemble the adhesions fibroblasts make to the extracellular matrix. Some extracellular matrix compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 102 publications
8
57
0
1
Order By: Relevance
“…40 This point is underscored by several proteins classically thought to be "structural" FA components: vinculin is selectively activated by changes in head-tail interactions regulated by binding to talin 41,42 ; ␣-actinin forms a signaling complex with the Abl/Arg kinase adapter ArgBP2 43 ; and paxillin integrates diverse inputs including tyrosine kinases and Rho family regulators. 44 Additionally, FAs contain a rich diversity of enzymatically active proteins that direct cell fate, shape, and motion (see Figure 2).…”
Section: Molecular Signal Generatorsmentioning
confidence: 99%
“…40 This point is underscored by several proteins classically thought to be "structural" FA components: vinculin is selectively activated by changes in head-tail interactions regulated by binding to talin 41,42 ; ␣-actinin forms a signaling complex with the Abl/Arg kinase adapter ArgBP2 43 ; and paxillin integrates diverse inputs including tyrosine kinases and Rho family regulators. 44 Additionally, FAs contain a rich diversity of enzymatically active proteins that direct cell fate, shape, and motion (see Figure 2).…”
Section: Molecular Signal Generatorsmentioning
confidence: 99%
“…104 - 105 Most cells, including vascular endothelial cells, interact with their substrata in specialized areas of the cell known as focal adhesion sites. 116 - 119 These sites are enriched on the ECM side in attachment proteins, such as fibronectin and heparan sulfate proteoglycans. and on the cytoplasmic side in actin microfilaments.…”
Section: Cell Adhesionmentioning
confidence: 99%
“…and on the cytoplasmic side in actin microfilaments. 119 Colocalization of HSPG with cytoskeletal elements such as actin suggests that proteoglycans may influence cell adhesion through association with the cytoskeleton. 111116 Recent studies have shown that the integrity of actin stress filaments is critical for endothelial cell adherence when exposed to shear stress.…”
Section: Cell Adhesionmentioning
confidence: 99%
“…6). Structurally, SAM consists primarily of tight focal contacts and a subset of a close contacts (for review see Lark et al, 1985), which are distinguishable both in proximity to the substratum surface and in protein composition (for detailed structural analysis of these contact regions see Krueger et al, 1984;Ben-Ze'ev, 1985;Burridge et al, 1987). Cell-substrate contact sites were also prepared in the present study using the saponinextraction procedure.…”
Section: Discussionmentioning
confidence: 99%